Decreasing Student Disciplinary Referrals and Increasing Reading Achievement: Positive Behavioral Support - Griffin, Tracey T. (My University, 2014)
Positive Behavioral Support (PBS) is an effective practice for decreasing student misbehavior, as measured through lower office disciplinary referral rates and increased academic achievement (Lewis & Sugai, 1999). An elementary-school PBS team was developed to implement a systematic, problem-solving approach with early intervention techniques in order to reduce office referral rates and increase student achievement. Goals included teaching behavioral expectations, developing consistent behavior lesson plans for teachers, defining and reinforcing appropriate behavioral expectations, and implementing a reward system for students exhibiting socially acceptable behavior. Disciplinary data from the PBS school showed a strong decrease in the number of disciplinary office referrals following implementation of the support program when compared to a non-PBS school. Additionally, for students with three or more disciplinary office referrals (repeat offenders), there was no significant difference for the first year referral rates, indicating the two study groups, PBS and non-PBS, were similar in respect to incidents prior to program implementation. After implementation of PBS, statistical differences, and large effect-size estimates of this 3-year analysis, were found between groups. No statistical differences or differences in effect-size estimates of any significance were found regarding implementation of PBS and reading performance. Qualitative analysis from staff surveys produced three general themes: PBS positively impacted the overall climate of the school; PBS positively impacted school discipline records by reducing office referral rates; and, PBS did not appear to impact student reading achievement.
I. INTRODUCTION - 1 Overview - 1 Statement of the Problem - 5 Theoretical Framework - 6 Description of the PBS Implementation - 8 Purpose of the Study - 11 Research Questions - 11 Significance of the Study - 12 Definition of Terms - 13 Summary - 14 Organization of the Study - 15 II. LITERATURE REVIEW - 16 Overview - 16 Historical Perspective of PBS in Education - 17 PBS as an Applied Science - 19 Social Outcomes Associated with School Success - 21 Implementing Schools Wide PBS - 23 Three Tiered Model of PBS - 24 Challenges of Implementing PBS - 27 Utilizing Office Referrals as School Level Data -29 Effects of PBS on Reading Achievement -33 Standardized Test for the Assessment of Reading - 35 Summary - 37 III. METHODOLOGY - 40 Overview - 40 Research Design - 41 Quantitative Methods - 41 Qualitative Methods - 42 Validity and Reliability - 42 Setting and Sample - 44 Instrumentation - 44 Data Collection and Analysis - 46 Student Data - 46 Staff Survey Data - 47 Ethical Considerations and Limitations - 49 Summary - 50 IV. RESULTS - 51 Overview - 51 Hypothesis Testing - 52 Research Question 1 - 53 Research Question 2 - 56 Research Question 3 - 58 Research Question 4 - 59 Summary - 60 V. DISCUSSION AND CONCLUSIONS -62 Overview - 62 Purpose of the Study - 63 Theoretical Framework - 63 Methodology - 68 Findings and Discussion - 70 Limitations - 73 Suggestions for Future Research -75 REFERENCES - 77 APPENDIX A: School Office Referral -93 APPENDIX B: School Manual for Positive Behavioral Support - 95 APPENDIX C: PBIS Survey - 116 APPENDIX D: Institutional Review Board Approval - 120 APPENDIX E: 2009-10 Discipline Summary Chart - 122 APPENDIX F: 2010-11 Discipline Summary Chart - 124 APPENDIX G: 2011-12 Discipline Summary Chart - 126
Keywords: Positive Behavioral Support (PBS); Education; Student Disipline; Literacy; Elementary Schools